INSTAGRAM SEBAGAI MEDIA KREATIVITAS BERPUISI DI TENGAH PANDEMI - Siti Nur Azizah; Rianto Rianto (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2021)
During a pandemic situation that is still hitting, the role of social media is very influential on the development of literature in Indonesia. With the advancement of technology, literature is not only found in spoken or written form in books, but also in digital form with the Instagram timeline (veranda) social media. This study aims to explain the strategic role of Instagram in the creative process of poetry during a pandemic. This study uses descriptive qualitative methods and data collection techniques by way of screenshots on the researcher's device. The data sources are taken from two Instagram accounts that are concerned with the development of poetry, namely the Wikipuisi and Kongsipuisi accounts. The results showed that the two accounts greatly influenced the existence of poetry on Instagram with the number of followers reaching 12,400 and 274,000, respectively. In addition, Instagram is also a means for famous poets to re-publish their works and an arena for the creativity of new writers who want to display their work.